"Nova burguesia nacional" nos governos Lula e Dilma? : uma crítica às teses de Armando Boito Júnior (2003-2013) - Oliveira, Raphael Rodrigues de (2016)
The aim of this work is presents a critical analyze Armado Boito Junior’s thesis about the development of a new national bourgeoisie during presidential governments of Luiz Inácio Lula da Silva (2003 – 2010) and the first mandate of Dilma Roussef (2011 – 2014). First, presents a bibliographic review of the author’s writes about the theme. In second, a research about the stockholder structure of the representative companies of the new national bourgeoisie. By the end, critic questions in basis of authors that treat financialization thematic, and by the understanding of questions about the historical formation of Brazil, according Caio Prado Júnior.